HUBUNGAN PENGETAHUAN, POLA ASUH DAN STATUS GIZI DENGAN PERKEMBANGAN KOGNITIF DI KABUPATEN PADANG PARIAMAN - Detty Afriyanti (HUMAN CARE JOURNAL, 2016)
In Indonesia, 5-10% of children are estimated to experience developmental delays. Data on the incidence of developmental delays is not known with certainty, but it is estimated that around 1-3% of children under 5 years experience general developmental delays. The total population of Indonesia is 255,461,686 people, and the number of children is 9,451,943. The number of preschool children is 36,433 people out of a population of 971,511 people or around (3.75%). The research objective is the relationship of the level of knowledge, parenting and nutritional status with the cognitive development of children in Padang Pariaman District.The design of this research is descriptive analytic. The study was conducted at SDN 03 Ulakan Tapakis from June to July 2016. The population in this study were all mothers who had Children from Class I to Class VI in Elementary School as many as 64 people. Data collection was carried out by questionnaire and analyzed by univariate and bivariate.Based on the results of the study, found 56.3% of children's cognitive development is not good; 60.9% of your level of knowledge is not good; 75% parenting is not good; 60.9% of children's nutritional status is not good. Furthermore, there is a relationship between the level of knowledge, parenting, and nutritional status with the development of children aged 6 to 12 years at SDN 03 Ulakan TapakisBased on the results of the study, it is expected that mothers increase knowledge about nutritional status and improve nutritional and parenting patterns to avoid child development disorders